Hybrid structures for surface acoustic wave devices and related methods of manufacture

By using a piezoelectric material working layer in the surface acoustic wave device, a sintered composite layer matching the low thermal expansion coefficient support substrate and acoustic impedance, the parasitic sound wave problem is solved, and the frequency and temperature coefficient are improved and thickness compatibility is achieved.

CN120379511APending Publication Date: 2025-07-25SOITEC SA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510462420.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-03-30
Filing Date
2019-03-13
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

In existing surface acoustic wave devices, parasitic sound waves have a negative impact on frequency characteristics, and the total thickness of the hybrid substrate is incompatible with the demand in the mobile phone market.

Method used

The working layer of piezoelectric material is assembled with the support substrate. The intermediate layer is made of sintered composite layer formed by powders of different materials. The acoustic impedance matching and particle size design is designed to reduce parasitic sound waves. The thermal expansion coefficient of the support substrate is lower than that of the working layer.

Benefits of technology

Effectively reduce or eliminate parasitic sound waves, improve frequency and temperature coefficient, and be compatible with the thickness requirements of the mobile phone market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120379511A_ABST
    Figure CN120379511A_ABST
Patent Text Reader

Abstract

The invention relates to a hybrid structure for a surface acoustic wave device and an associated manufacturing method, said hybrid structure (10) comprising: a useful layer (1) of piezoelectric material joined to a support substrate (2) having a lower coefficient of thermal expansion than the useful layer (1); and an intermediate layer (3) arranged between the useful layer (1) and the support substrate (2). The intermediate layer is a sintered composite layer (3) formed from a powder of at least a first material and a second material, the second material being different from the first material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the patent application for invention with the original application number 201980018383.6 (filing date: March 13, 2019, international application number: PCT / FR2019 / 050540, invention title: Hybrid structure for surface acoustic wave devices and related manufacturing method). Technical Field

[0002] The present invention relates to the field of surface acoustic wave devices. In particular, the present invention relates to a hybrid structure suitable for manufacturing surface acoustic wave devices. Background Art

[0003] The structure of acoustic resonators such as surface acoustic wave (SAW) devices uses one or more interdigital transducers produced on a piezoelectric substrate to convert an electrical signal into an acoustic wave and vice versa. Such SAW devices or resonators are typically used in filter applications. Radio frequency (RF) SAW technology provides excellent performance (such as high isolation and low insertion loss). For this reason, RF SAW technology is used in RF duplexers in wireless communication applications.

[0004] The improvement of the performance of RF SAW devices is achieved especially by obtaining a frequency response that is stable with respect to temperature. The dependence of the operating frequency of a SAW device on temperature or the temperature coefficient of frequency (TCF) depends, on the one hand, on the change in the spacing between the interdigital electrodes of the transducer (which change is usually due to the relatively high coefficient of thermal expansion (CTE) of the piezoelectric substrate used); on the other hand, since the expansion or contraction of the piezoelectric substrate is accompanied by an increase or decrease in the surface acoustic wave velocity, the TCF depends on the temperature coefficient of velocity. In order to minimize the temperature coefficient of frequency (TCF), an object is therefore to minimize the expansion / contraction of the piezoelectric substrate (especially in the surface region where the acoustic wave propagates).

[0005] The article "Recent development of temperature-compensated SAW devices" by K. Hashimoto, M. Kadota et al., IEEE Ultrason. Symp. 2011, pages 79 to 86, 2011 outlines the methods commonly used to overcome the problem of the dependence of the frequency response of SAW devices on temperature.

[0006] An advantageous method consists in using a hybrid substrate (e.g., a hybrid substrate composed of a piezoelectric material layer located on a silicon substrate). The low CTE of silicon can limit the expansion / contraction of the piezoelectric layer with respect to temperature. In the case of a piezoelectric layer of lithium tantalate (LiTaO3), the above article states that a ratio of the thickness of LiTaO3 to the thickness of the silicon substrate of 10 can suitably improve the temperature coefficient of frequency (TCF). One of the drawbacks of this method is the presence of parasitic acoustic waves (referred to as "stray acoustic modes" in the article by B.P. Abbott et al., "Characterization of bonded wafer for RF filters with reduced TCF", Proc. 2005 IEEE International Ultrasonics Symposium, Sept 19 - 21, 2005, pp. 926 - 929), which have a negative impact on the frequency characteristics of resonators produced on the hybrid substrate. These parasitic resonances are particularly related to the parasitic reflections of the main acoustic wave (which mainly propagates in the surface region of the LiTaO3 layer) at the interface below (especially including the interface between LiTaO3 and silicon). One solution to reduce these parasitic resonances is to increase the thickness of the LiTaO3 layer; since this also requires increasing the thickness of the Si substrate in order to maintain the improvement of the TCF, the total thickness of the hybrid substrate is no longer compatible with the requirement of reducing the final component thickness, especially for meeting the needs of the mobile phone market. Another solution proposed by K. Hashimoto et al. (the above article) is to roughen the lower surface of the LiTaO3 layer (at the bonding interface with the substrate) to limit the reflection of acoustic waves at this lower interface.

[0007] Object of the Invention

[0008] An object of the present invention is to provide an alternative solution to the solutions of the prior art. An object of the present invention is in particular to provide a hybrid structure that enables the reduction and / or elimination of said parasitic acoustic waves. Summary of the Invention

[0009] The present invention relates to a hybrid structure for a surface acoustic wave device, the hybrid structure comprising: a working layer of a piezoelectric material, the working layer being assembled with a support substrate, the support substrate having a lower coefficient of thermal expansion than the working layer; and an intermediate layer located between the working layer and the support substrate. The remarkable feature of the hybrid structure is that the intermediate layer is a sintered composite layer formed from powders of at least a first material and a second material different from the first material.

[0010] Advantageous features obtained according to the present invention, alone or in combination:

[0011] · The acoustic impedance of the first material is similar to that of the working layer; the ratio of the acoustic impedance of the working layer to that of the second material is greater than 2; and the average size of the particles of the powder of the first material and the second material is greater than or equal to one quarter of the wavelength of the acoustic signal intended to propagate at the surface of the surface acoustic wave device.

[0012] · The first material and the second material are selected to form an acoustic impedance matching layer between the working layer and the support substrate; the average size of the particles of the powder of the first material and the second material is less than one quarter of the wavelength of the acoustic signal intended to propagate at the surface of the surface acoustic wave device.

[0013] · The support substrate comprises a material selected from silicon, glass, silicon dioxide, sapphire, alumina, aluminum nitride.

[0014] · The working layer comprises a piezoelectric material selected from lithium tantalate (LiTaO3), lithium niobate (LiNbO3), quartz, zinc oxide (ZnO).

[0015] · The first material and the second material are selected from silicon oxide, silicon nitride, silicon, silicon carbide, alumina, germanium, sapphire, zirconium.

[0016] · The composite layer has a thickness between a few hundred nanometers and a few tens of micrometers.

[0017] The invention also relates to a method for manufacturing a hybrid structure for a surface acoustic wave device, the method comprising the steps of:

[0018] i) Providing a working layer of piezoelectric material and a support substrate, the thermal expansion coefficient of the support substrate being lower than that of the working layer;

[0019] working layer;

[0020] ii) Depositing a layer formed of a powder mixture of at least a first material and a second material, different from the first material, on a first face of the working layer and / or on a first face of the support substrate;

[0021] iii) Sintering the layer formed of the powder mixture to obtain a sintered composite layer firmly attached to the first face of the working layer and / or to the first face of the support substrate;

[0022] iv) Assembling the working layer and the support substrate such that the composite layer is located between the working layer and the support substrate.

[0023] iv) Assembling the working layer and the support substrate such that the composite layer is located between the working layer and the support substrate.

[0024] Advantageous features obtained according to the invention, individually or in combination:

[0025] ·Before depositing the layer formed from the powder mixture according to step ii), the first face of the working layer and / or the first face of the support substrate comprises a protective layer.

[0026] ·The protective layer is formed from at least one material selected from silicon nitride, silicon oxynitride, silicon oxide and aluminium oxide.

[0027] ·The powder mixture is in the form of a viscous paste and the deposition of the layer formed from the mixture in step ii) is effected by spin coating.

[0028] ·After depositing the layer formed from the powder mixture, a low-temperature heat treatment is carried out in order to expel at least one liquid component of the viscous paste.

[0029] ·Before the assembly step iv), a bonding layer is deposited on the sintered composite layer.

[0030] ·The working layer provided in step i) is a piezoelectric material donor substrate.

[0031] ·The manufacturing method comprises a step v): thinning the donor substrate to the desired thickness of the working layer for manufacturing the acoustic wave device. Description of the Drawings

[0032] With reference to the drawings, other features and advantages of the invention will become apparent from the following detailed description, in the

[0033] drawings:

[0034] Figure 1 There is shown a hybrid structure according to the invention;

[0035] Figure 2a and Figure 2b There is shown a hybrid structure according to the invention;

[0036] Figure 3 There is shown a hybrid structure according to the invention, including a SAW device;

[0037] Figures 4a to 4e There is shown a method for manufacturing a hybrid structure according to the invention. Detailed Description

[0038] In the descriptive part, the same reference numerals as in the drawings may be used for elements of the same nature. The drawings are schematic representations and, for the sake of readability, are not drawn to scale. In particular, the thickness of the layers along the z-axis is not in proportion to the lateral dimensions along the x-axis and the y-axis.

[0039] The present invention relates to a hybrid structure 10 suitable for manufacturing surface acoustic wave (SAW) devices, and the hybrid structure 10 is particularly suitable for manufacturing devices having frequencies in the range from several tens of MHz to several tens of GHz.

[0040] As Figure 1 shown, the hybrid structure 10 according to the present invention includes a working layer 1 of a piezoelectric material, and the working layer 1 has a first surface 1a and a second surface 1b. Since the working layer 1 will be used for the subsequent production of surface acoustic wave devices, the working layer 1 is thus named. As shown below, Table 1a presents a list of suitable materials for forming the sintered composite layer of the hybrid structure according to the present invention, and Table 1b presents a list of materials for forming the working layer of the hybrid structure according to the present invention. For example, the working layer 1 of the hybrid structure 10 can be composed of materials selected from the following group: lithium tantalate LiTaO3 (LTO in Table 1b), lithium niobate LiNbO3 (LNO in Table 1b), aluminum nitride AlN (Table 1b), zinc oxide (ZnO).

[0041]

[0042] Table 1a

[0043]

[0044] Table 1b

[0045] The hybrid structure 10 further includes an intermediate layer 3 located below the working layer 1 (along the Figure 1 shown z-axis). The intermediate layer is a sintered composite layer 3 formed from powders of at least two different materials. The sintered layer should be understood to refer to a layer produced by the consolidation of a powder mixture: such consolidation is obtained by inputting thermal energy and optionally mechanical energy, but at least one of the powdery materials in the unmelted mixture of powdery materials. Therefore, the sintered nature of the composite layer can be detected by structural analysis of the layer (for example, by scanning electron microscopy). The particles or grains of the material powders seem to be welded together, and the density of the composite layer depends on the degree of compaction of the mixture during the input of energy for consolidation.

[0046] The particles of the powders of the various materials forming the sintered composite layer 3 have sizes following a typical Gaussian distribution. In the remainder of the specification, the average size of the particles will be analogous to the equivalent average diameter of the particles of a given material. The average size of the particles can generally vary between several tens of nanometers and several micrometers.

[0047] The sintered composite layer 3 can in particular be formed from at least a first material and a second material selected from silicon oxide, silicon nitride, silicon, silicon carbide, aluminum oxide, germanium, sapphire, zirconium, some of whose properties are shown in Table 1.

[0048] The sintered composite layer 3 may optionally include three or more different materials.

[0049] Depending on the implementation, the sintered composite layer 3 has a thickness between a few hundred nanometers and a few micrometers.

[0050] Finally, the hybrid structure 10 includes a support substrate 2, which has a coefficient of thermal expansion lower than that of the working layer 1, is located below the composite layer 3 (along the Figure 1 shown z-axis), and can limit the expansion / contraction of the working layer 1 with respect to temperature (and thus improve the frequency temperature coefficient of the device to be produced on the working layer 1). The support substrate 2 can in particular be made of a material selected from the group consisting of silicon, III-V semiconductors, silicon carbide, glass, and sapphire.

[0051] As Figure 2a and Figure 2b shown, the hybrid structure 10 preferably includes an additional layer 4, which is located on the first surface 1a of the working layer 1 and / or on the first surface 2a of the support substrate 2, and may be located on the second surface 2b of the support substrate 2 and on the edge of the substrate 2 ( Figure 2b ). As will be seen in the description of the method for manufacturing the hybrid structure 10, these additional layers 4 in particular have the effect of protecting the support substrate 2 and / or the working layer 1 from the diffusion of impurities contained in the sintered composite layer 3 or present during the production of the layer 3.

[0052] The hybrid structure 10 according to the present invention is suitable for manufacturing surface acoustic wave (SAW) devices, and the SAW devices in particular include metal electrodes 20 on the working layer 1, and acoustic signals propagate between the metal electrodes 20 (represented by Figure 3 the white arrows in), and in the (x, y) plane, the metal electrodes 20 are close to the surface of the second surface 1b of the working layer 1.

[0053] According to a first embodiment of the hybrid structure 10 of the present invention, the sintered composite layer 3 is configured to maximize the diffusion of the incident acoustic wave, which is generated by the acoustic signal and will propagate into the composite layer 3 in the volume of the working layer 1.

[0054] To this end, in the sintered composite layer 3 formed of powders of at least a first material and a second material, the acoustic impedance of the first material is similar to that of the working layer 1. The term "similar" is understood to mean having a maximum deviation of ±20% near the acoustic impedance value of the working layer 1, and the deviation is preferably less than ±15%, or even ±10%. For example, for the working layer 1 made of LiTaO3, the first material may be alumina, and the acoustic impedance of alumina (40.6×10 6 Pa.s / m) is similar to the acoustic impedance of lithium tantalate (44.8×106 is substantially the same as Pa.s / m).

[0055] In addition, the ratio of the acoustic impedance of the working layer 1 to the acoustic impedance of the second material of the sintered composite layer 3 is selected to be greater than or equal to 2 in order to ensure that the reflection coefficient is greater than 10%. For example, if the first material is lithium tantalate (44.8×10 6 Pa.s / m), the second material may be SiO2, and the acoustic impedance of SiO2 is 13.2×10 6 Pa.s / m, so that a reflection coefficient of approximately 30% can be obtained at the interface between the particles of the composite layer 3 and reflection (diffusion) occurs in multiple directions.

[0056] Finally, the particle size of the powders of the first material and the second material is greater than or equal to one quarter of the wavelength of the incident acoustic wave. This feature ensures that the incident acoustic wave can be affected by the particles. For example, for an incident acoustic wave having a wavelength of approximately 6 micrometers (i.e., a frequency of approximately 1 GHz), the average size of the particles will be selected to be approximately 2 micrometers. Then, the sintered composite layer 3 has a thickness greater than 5 micrometers, or even greater than 10 micrometers.

[0057] If there is an additional layer 4 between the working layer 1 and the composite layer 3, the acoustic impedance of the additional layer 4 will have to be close to the acoustic impedance of the working layer 1 in order to limit the parasitic reflections between these two layers. For the working layer 1 made of LiTaO3, for example, alumina can be used, and the acoustic impedance of alumina (40.6×10 6 Pa.s / m) is close to the acoustic impedance of LiTaO3, which results in a reflection of less than 0.5%.

[0058] The sintered composite layer 3 according to the first embodiment enables the incident wave to be diffused in multiple directions and thus greatly limits the component reflected towards the electrode 20 of the surface acoustic wave device.

[0059] According to a second embodiment of the hybrid structure 10 of the present invention, the sintered composite layer 3 is configured to maximize the transmission of the incident acoustic wave, which is generated by an acoustic signal and will propagate in the volume of the working layer 1 to the composite layer 3.

[0060] To this end, in the sintered composite layer 3 formed of powders of at least a first material and a second material, the first material and the second material are selected to form an acoustic impedance matching layer between the working layer 1 and the support substrate 2. Forming an acoustic impedance matching layer implies that the average acoustic impedance of the composite layer 3 is approximately equal to the square root of the product of the acoustic impedance of the working layer 1 and the acoustic impedance of the support substrate 2:

[0061]

[0062] It should be remembered that the acoustic impedance Z of a material is expressed as:

[0063] ″ = v × ρ

[0064] where v is the velocity of sound waves in the material and ρ is the density of the material.

[0065] In the case of the composite layer 3, the volume fractions V1 and V2 of the various materials forming the composite layer 3 are considered; thus, the acoustic impedance of the composite layer 3 (in the case of two materials) can be evaluated according to the following formula:

[0066] Z 复合层 = (v1 × V1 + v2 × V2) × (ρ1 × V1 + ρ2 × V2)

[0067] where ρ1 and ρ2 are the densities of the first material and the second material respectively, and v1 and v2 are the velocities of sound waves in the first material and the second material respectively.

[0068] The volume fractions V1 and V2 are defined by the proportions of the various materials in the composite layer 3.

[0069] For example, the first material can be Al2O3 and the second material is SiO2, which are present in the composite layer in proportions of 65% and 35% respectively. Thus, the impedance of the composite layer 3 can be about 30×10 6 Pa.s / m.

[0070] Furthermore, according to this second embodiment, the average size of the particles of the powders of the first material and the second material is less than one quarter of the wavelength of the incident sound waves. This feature ensures that the incident sound waves treat the composite layer as an almost homogeneous medium. For example, for incident sound waves having a wavelength of about 7.5 microns (i.e., a frequency of about 800 MHz), the average size of the particles can be chosen to be about 0.5 microns. The sintered composite layer 3 can have a thickness of several microns.

[0071] If there is an additional layer 4 between the working layer 1 and the composite layer 3, the acoustic impedance of this additional layer 4 will have to be close to the acoustic impedance of the working layer 1 in order to limit the parasitic reflections between these two layers. For the working layer 1 made of LiTaO3, for example, alumina can be used, and the acoustic impedance of alumina (40.6×10 6 Pa.s / m) is close to the acoustic impedance of LiTaO3, which results in a reflection of less than 0.5%.

[0072] If there is an additional layer 4 between the composite layer 3 and the support substrate 2, the acoustic impedance of this additional layer 4 will have to be close to the acoustic impedance of the support substrate 2 in order to limit the parasitic reflections at the additional layer / support substrate interface. For the support substrate made of Si, for example, silicon nitride can be used, and the acoustic impedance of silicon nitride (~22×10 6 Pa.s / m) is close to the acoustic impedance of Si, which results in a reflection of less than 0.5%.

[0073] The sintered composite layer 3 according to the second embodiment can promote the transmission of incident sound waves (through acoustic impedance matching) that are normally reflected at the interface of the hybrid structure from the working layer 1 to the substrate 2: thus, parasitic reflections that have a negative impact on the frequency characteristics of SAW devices produced on the hybrid structure 10 can be reduced.

[0074] According to a variant of the various embodiments applicable to the hybrid structure 10, the sintered composite layer 3 has good dielectric properties (resistivity greater than 1E7 ohms.cm) and a low equivalent dielectric constant (usually less than the dielectric constant of silicon, 11 F / m) in order to provide electrical insulation equivalent to that of several micrometers of silicon oxide. Such a sintered composite layer 3 can in particular improve the linearity of surface acoustic wave devices in the radio frequency field.

[0075] According to another variant of the various embodiments applicable to the hybrid structure 10, the sintered composite layer 3 has mobile charge trapping properties. This feature can trap and thus cancel out charges that may appear in the upper part of the support substrate 2 due to the presence of fixed charges in one of the upper layers (the additional layer 4 or the working layer 1). In order to have this trapping feature, one of the materials of the particles constituting the composite layer 3 can be silicon.

[0076] The present invention also relates to a method of manufacturing a hybrid structure 10 for a surface acoustic wave device. The method includes a first step (denoted by i)) of providing a working layer 1 of piezoelectric material. According to an advantageous embodiment, the working layer 1 is in the form of a donor substrate 1' of piezoelectric material having standard thickness and diameter for the microelectronics industry ( Figure 4a ).

[0077] The first step also includes providing a support substrate 2 having a lower coefficient of thermal expansion than that of the donor substrate 1' (i.e., also lower than the coefficient of thermal expansion of the working layer 1).

[0078] The manufacturing method according to the present invention includes a second step (denoted by ii)), which includes depositing a layer 3' formed from a powder mixture of at least a first material and a second material different from the first material on the first face 1a of the working layer 1 (or of the donor substrate 1') and / or on the first face 2a of the support substrate 2. In Figure 4b the example shown, the layer 3' of the powder mixture is deposited on the first face 2a of the support substrate 2. The layer 3' can be deposited on the first face 1a of the working layer 1; the layer 3' can also be deposited separately on each of the first face 1a of the working layer 1 and the first face 2a of the support substrate 2.

[0079] Advantageously, the first face 2a of the support substrate 2 comprises a protective layer 4a produced prior to the deposition of the layer 3' of the powder mixture. The protective layer 4a can even completely encapsulate the support substrate 2 (i.e., cover the back face 2b of the support substrate 2 and the edges of the support substrate 2).

[0080] Alternatively, if the layer 3' of the powder mixture is deposited on the working layer 1 (or the donor substrate 1'), the protective layer will be deposited at least on the first face 1a of the working layer 1 (or the donor substrate 1').

[0081] Preferably, the protective layer 4a is formed of at least one material selected from silicon nitride, silicon oxynitride, silicon oxide, and aluminum oxide. The protective layer 4a can be produced by various known chemical deposition techniques. Diffusion of impurities contained in the layer 3' into the support substrate 2 (or the working layer 1) can be avoided or at least limited.

[0082] According to a variant of the first embodiment, the powder mixture is in the form of a viscous paste.

[0083] Such a paste is generally obtained by adding a liquid compound of the solvent type (especially an alcohol, such as ethanol) to the dry powder mixture. Generally, the powder used contains particles having an average size between several tens of nanometers and several micrometers.

[0084] Alternatively, the powder mixture can be mixed into a matrix of the silicon-based polymer type (for PDC of polymer-derived ceramics), which matrix is capable of being converted into a ceramic at high temperature. Note that in the case of the layer 3' having a PDC matrix, the sintered composite layer 3 obtained subsequently will include a first material and a second material from the powder mixture, and will also include silicon from the conversion of the matrix into a ceramic.

[0085] The deposition of the layer 3' formed from the mixture in step ii) is preferably carried out by spin coating (or dip coating) or by screen printing through a mask.

[0086] The viscosity of the paste is adjusted by the ratio of the powder / liquid compound (solvent and / or polymer). The viscosity of the paste is selected to be able to deposit the layer 3' uniformly with a thickness that can vary from several hundred nanometers to several micrometers.

[0087] After the deposition of the layer 3', heat treatment is carried out at a low temperature (e.g., between 150 °C and 400 °C), so that the solvent can be discharged from the layer 3', and any subsequent degassing during the process (especially after the assembly step (described below)) can be avoided.

[0088] According to a variant of the second embodiment, the powder mixture is in dry powder form and is deposited as layer 3' on the first face 2a of the support substrate 2 (alternatively deposited on the face 1a of the donor substrate 1'). The shaping of this layer 3' can be carried out by compression molding or hot isostatic pressing. In both cases, a compressive stress is applied to layer 3' to firmly attach the particles of the mixture powder to each other and to the first face 2a. A special tool is required to hold the powder mixture on the substrate and apply a uniform compressive stress over the entire surface of the substrate.

[0089] The manufacturing method according to the invention comprises a third step (denoted by iii), which includes sintering the layer 3' formed from the powder mixture in order to obtain a sintered composite layer 3 firmly attached to the first face 2a of the support substrate 2 ( Figure 4c ).

[0090] Sintering is generally carried out at a high temperature typically above 1000 °C for a duration that can vary from a few hours to about 24 hours. However, the sintering temperature is kept below the melting point of at least one of the powders comprised in layer 3'. Under the thermal action, the particles of the powder are welded together, which forms the cohesion of the resulting composite layer 3. The composite layer 3 is also firmly attached to the first face 2a of the support substrate 2.

[0091] Optionally, sintering can additionally be carried out under mechanical stress, which can further compact the composite layer 3.

[0092] Thus, the sintered composite layer 3 consists at least of particles of a first material and a second material. Between the particles, depending on the degree of compaction, there can be more or fewer interstitial spaces (or spaces containing the ceramic obtained from the PDC matrix). Depending on the particle size distribution, the volume fraction of these spaces can reach 50%, and more preferably remains below 25%, or even remains below 15%, especially in order to ensure good mechanical strength of the composite layer 3. For the sake of simplicity, this interstitial volume fraction has not been considered in the embodiments of the hybrid structure 10 described above; this interstitial space can be considered as a third material in addition to the first and second materials forming the particles.

[0093] The thickness of the layer 3' deposited in step ii) is chosen in order to obtain the desired thickness of the sintered composite layer 3. In fact, depending on the type of layer 3' deposited (in the form of a paste with solvent and / or polymer or in dry form), the thickness reduction during the sintering step will be greater or smaller. The volume of layer 3' can be reduced by about 10% to 30%.

[0094] The manufacturing method according to the present invention includes a fourth step (denoted by iv), which includes assembling the working layer 1 (donor substrate 1') and the support substrate 2 such that the sintered composite layer 3 is located between the working layer 1 and the support substrate 2 ( Figure 4d ).

[0095] Preferably, before the assembling step iv), a bonding layer 4b is deposited on the composite layer 3. For example, a silicon oxide layer can be deposited on the free surface of the composite layer 3. On the one hand, the bonding layer 4b provides encapsulation of the sintered composite layer 3, thus avoiding or at least limiting the risk of contamination between the layers of the hybrid structure 10; on the other hand, the bonding layer 4b may be advantageous for allowing conventional surface preparation of components not specific to the sintered composite layer 3.

[0096] Preferably, the assembling step is carried out by directly bonding the two contacting surfaces by molecular adhesion (i.e., the first surface 1a of the working layer 1 (or the donor substrate 1') and the free surface of the composite layer 3 from Figure 4c in the example). The principle of molecular adhesion, which is well known in the prior art, will not be described in further detail here.

[0097] Alternatively, the assembling can be carried out by adding a layer of adhesive material or by any other bonding technique suitable for the intended application.

[0098] For most assembling methods, the substrates to be assembled will need to have good surface finish (cleanliness, low roughness, etc.).

[0099] The manufacturing method according to the present invention may further include a fifth step (denoted by v), which includes thinning the donor substrate 1' to the desired thickness of the working layer 1 for manufacturing the acoustic wave device ( Figure 4e ). For example, this step may include mechanical grinding followed by dry or chemical mechanical polishing, thereby ensuring good surface finish of the working layer 1. Various cleaning procedures can be applied during or after the thinning step to ensure the quality and cleanliness of the final hybrid structure 10.

[0100] The thinning of the donor substrate 1' can be carried out by any other known technique (especially Smart process or other techniques for producing thin layers) to obtain the working layer 1.

[0101] Of course, the present invention is not limited to the described embodiments, and examples and variant embodiments can be introduced without departing from the scope of the present invention defined by the claims.

Claims

1. A hybrid structure (10) for a surface acoustic wave device, the hybrid structure (10) comprising: The working layer (1) of a piezoelectric material, the working layer (1) being assembled with a support substrate (2), the support substrate (2) having a lower coefficient of thermal expansion than the working layer (1); and an intermediate layer (3), the intermediate layer (3) being located between the working layer (1) and the support substrate (2), the intermediate layer (3) being a sintered composite layer formed from powders of at least a first material and a second material, the second material being different from the first material, the hybrid structure (10) being characterized in that: the first material and the second material are selected to form an acoustic impedance matching layer between the working layer (1) and the support substrate (2); the average size of the particles of the powders of the first material and the second material is less than a quarter of the wavelength of the acoustic signal intended to propagate at the surface of the surface acoustic wave device; 2. The hybrid structure (10) for a surface acoustic wave device according to claim 1, wherein, the support substrate (2) comprises a material selected from at least one of silicon, glass, silica, sapphire, alumina and aluminum nitride; 3. The hybrid structure (10) for a surface acoustic wave device according to claim 1 or 2, wherein, the working layer (1) comprises a piezoelectric material selected from at least one of lithium tantalate (LiTaO3), lithium niobate (LiNbO3), quartz and zinc oxide (ZnO); 4. The hybrid structure (10) for a surface acoustic wave device according to claim 1, wherein, the first material and the second material are selected from at least one of silicon oxide, silicon nitride, silicon, silicon carbide, alumina, germanium, sapphire, zirconium; 5. A method of manufacturing a hybrid structure (10) for a surface acoustic wave device, characterized in that, The method comprises the following steps: i) providing a working layer (1) of a piezoelectric material and a support substrate (2), the support substrate (2) having a lower coefficient of thermal expansion than the working layer (1); ii) depositing a layer (3') formed from a powder mixture of at least a first material and a second material, the second material being different from the first material, on the first face (1a) of the working layer (1) and / or on the first face (2a) of the support substrate (2), the first material and the second material being selected to form an acoustic impedance matching layer between the working layer (1) and the support substrate (2), and the average size of the particles of the powders of the first material and the second material being less than a quarter of the wavelength of the acoustic signal intended to propagate at the surface of the surface acoustic wave device; iii) sintering the layer (3') formed from the powder mixture to obtain a sintered composite layer (3) firmly attached to the first face (1a) of the working layer (1) and / or the first face (2a) of the support substrate (2); iv) assembling the working layer (1) and the support substrate (2) such that the composite layer (3) is located between the working layer (1) and the support substrate (2).

6. A method of manufacturing a hybrid structure (10) for a surface acoustic wave device according to claim 5, wherein, Before depositing the layer (3') formed from the powder mixture according to step ii), the first face (1a) of the working layer (1) and / or the first face (2a) of the support substrate (2) comprises a protective layer (4, 4a).

7. A method of manufacturing a hybrid structure (10) for a surface acoustic wave device according to claim 6, wherein, The protective layer (4, 4a) is formed from a material selected from at least one of silicon nitride, silicon oxynitride, silicon oxide and alumina; 8. A method of manufacturing a hybrid structure (10) for a surface acoustic wave device according to any one of claims 5 to 7, wherein, The powder mixture is in the form of a viscous paste, and depositing the layer (3') formed from the mixture in step ii) is carried out by spin coating.

9. The method for manufacturing a hybrid structure (10) for a surface acoustic wave device according to claim 8, wherein, After depositing the layer (3’) formed from the powder mixture, a low-temperature heat treatment is carried out to expel at least one liquid component of the viscous paste.

10. A method of manufacturing a hybrid structure (10) for a surface acoustic wave device according to any one of claims 5 to 7, wherein, Before assembly step iv), a bonding layer (4b) is deposited on the composite layer (3).

11. A method of manufacturing a hybrid structure (10) for a surface acoustic wave device according to any one of claims 5 to 7, wherein, The working layer (1) provided in step i) is a piezoelectric material donor substrate (1’).

12. The method for manufacturing a hybrid structure (10) for a surface acoustic wave device according to claim 11, the method comprising step v): thinning the donor substrate (1’) to a desired thickness for manufacturing the acoustic wave device of the working layer (1).

Citation Information

Cited By

  • High-temperature-resistant ultrasonic probe and preparation method thereof

    CN121499666A